Developing Task-Based English Speaking Materials for Internship vocational Students of Tourism Program in Sunrise Holiday Tour and Travel - Aris cita Wimanda (Language-Edu, 2019)
The purpose of the research was to (1) to know the material or product in speaking learning through task-based for internship vocational students in Sunrise Holiday Tour and Travel and (2) to develop the suitable English speaking textbook for Internship vocational students in Sunrise Holiday Tour and Travel. The design of this research study used Research and Development (R&D) in which this research aimed in developing an educational product such as textbook in tour guiding. The research subject was the internship students of Sunrise holiday tour and Travel. The procedure of development was classified into three steps (1) Pre-development, (2) development the draft after product, and (3) producing the final product. The pre-development was related to identify the problem by giving questionnaire to students and interviewing the instructor. Development the draft was gathered the information from the exciting book and the analysis and then developed it to draft of the product. The last procedure was producing the final product in which the researcher has done the editing material, asked the expert validation, revision the product and final product. The result of the research expressed that students loved the design of product and they could follow the instructions in every topic. Furthermore, the instructor said that the product was clear, appropriate and understandable textbook.